COVID-19-Era Trade Policy Interventions Affecting Medical Goods : Form, Frequency, Duration, and Scale - Evenett, Simon J. (World Bank, Washington, DC, 2022)
Drawing upon the findings of several trade policy surveillance initiatives, an account is presented here of government resort to trade restrictions and reforms affecting medical goods during the Coronavirus (COVID-19) pandemic. Some nations mustered effective public health responses early in the pandemic without resorting to trade restrictions. Some other governments quickly reversed export restrictions once their adverse side effects became evident. However, another group of nations have removed COVID-19 trade restrictions very slowly, if at all. These findings challenge the assumption that existing multilateral rules effectively regulate the crisis-era application of general exceptions to non-discrimination norms for goods trade. While the logic of those exceptions is to prevent multilateral trade obligations impeding public health responses, the COVID-19 pandemic has shown that these flawed rules on exceptions have attenuated the contribution of cross-border trade to pandemic response, in particular in those developing countries that source much medical goods from abroad.